A Myristoyl Amide Derivative of Doxycycline Potently Targets Cancer Stem Cells (CSCs) and Prevents Spontaneous Metastasis, Without Retaining Antibiotic Activity - Ózsvári, Béla; Magalhães, Luma G.; Latimer, Joe; Kangasmetsa, Jussi; Sotgia, Federica; Lisanti, Michael P. (Frontiers in Oncology, 2020)
Here, we describe the chemical synthesis and biological activity of a new Doxycycline derivative, designed specifically to more effectively target cancer stem cells (CSCs). In this analogue, a myristic acid (14 carbon) moiety is covalently attached to the free amino group of 9-amino-Doxycycline. First, we determined the IC50 of Doxy-Myr using the 3D-mammosphere assay, to assess its ability to inhibit the anchorage-independent growth of breast CSCs, using MCF7 cells as a model system. Our results indicate that Doxy-Myr is >5-fold more potent than Doxycycline, as it appears to be better retained in cells, within a peri-nuclear membranous compartment. Moreover, Doxy-Myr did not affect the viability of the total MCF7 cancer cell population or normal fibroblasts grown as 2D-monolayers, showing remarkable selectivity for CSCs. Using both gram-negative and gram-positive bacterial strains, we also demonstrated that Doxy-Myr did not show antibiotic activity, against Escherichia coli and Staphylococcus aureus. Interestingly, other complementary Doxycycline amide derivatives, with longer (16 carbon; palmitic acid) or shorter (12 carbon; lauric acid) fatty acid chain lengths, were both less potent than Doxy-Myr for the targeting of CSCs. Finally, using MDA-MB-231 cells, we also demonstrate that Doxy-Myr has no appreciable effect on tumor growth, but potently inhibits tumor cell metastasis in vivo, with little or no toxicity. In summary, by using 9-amino-Doxycycline as a scaffold, here we have developed new chemical entities for their further development as anti-cancer agents. These compounds selectively target CSCs, e.g., Doxy-Myr, while effectively minimizing the risk of driving antibiotic resistance. Taken together, our current studies provide proof-of-principle, that existing FDA-approved drugs can be further modified and optimized, to successfully target the anchorage-independent growth of CSCs and the process of tumor cell metastasis. Based on these findings, we propose that it may be more appropriate to refer to tumor-spheres as metasta-spheres, to better reflect the close relationship between 3D anchorage-independent growth and metastasis.